The Cardiac Syndecan-2 Interactome - Mathiesen, Sabrina Bech; Lunde, Marianne; Stensland, Maria; Martinsen, Marita; Nyman, Tuula A.; Christensen, Geir; Carlson, Cathrine Rein (Frontiers in Cell and Developmental Biology, 2020)
The extracellular matrix (ECM) is important in cardiac remodeling and syndecans have gained increased interest in this process due to their ability to convert changes in the ECM to cell signaling. In particular, syndecan-4 has been shown to be important for cardiac remodeling, whereas the role of its close relative syndecan-2 is largely unknown in the heart. To get more insight into the role of syndecan-2, we here sought to identify interaction partners of syndecan-2 in rat left ventricle. By using three different affinity purification methods combined with mass spectrometry (MS) analysis, we identified 30 novel partners and 9 partners previously described in the literature, which together make up the first cardiac syndecan-2 interactome. Eleven of the novel partners were also verified in HEK293 cells (i.e. AP2A2, CAVIN2, DDX19A, EIF4E, JPH2, MYL12A, NSF, PFDN2, PSMC5, PSMD11 and RRAD). The cardiac syndecan-2 interactome partners formed connections to each other and grouped into clusters mainly involved in cytoskeletal remodeling and protein metabolism, but also into a cluster consisting of a family of novel syndecan-2 interaction partners, the CAVINs. MS analyses revealed that although syndecan-2 was significantly enriched in fibroblast fractions, most of its partners were present in both cardiomyocytes and fibroblasts. Finally, a comparison of the cardiac syndecan-2 and -4 interactomes revealed surprisingly few protein partners in common.